2018
DOI: 10.1177/0269216318780223
|View full text |Cite
|
Sign up to set email alerts
|

How are physicians delivering palliative care? A population-based retrospective cohort study describing the mix of generalist and specialist palliative care models in the last year of life

Abstract: Background:To enable coordinated palliative care delivery, all clinicians should have basic palliative care skill sets (‘generalist palliative care’). Specialists should have skills for managing complex and difficult cases (‘specialist palliative care’) and co-exist to support generalists through consultation care and transfer of care. Little information exists about the actual mixes of generalist and specialist palliative care.Aim:To describe the models of physician-based palliative care services delivered to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 11 publications
2
68
0
Order By: Relevance
“…4 Our data do not support or refute either position, but as in other jurisdictions where MAiD is legal, we found that most MAiD recipients were followed by a palliative care clinician before death, 14,15,21,25 whereas only a minority of Ontario residents are followed by palliative care clinicians before they die. 26 This may allay fears that people are turning to MAiD because they cannot access palliative care. It may also suggest that people may be seeking MAiD to alleviate a type of suffering (e.g., existential distress 27 ) that may not be effectively treated by palliative care clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…4 Our data do not support or refute either position, but as in other jurisdictions where MAiD is legal, we found that most MAiD recipients were followed by a palliative care clinician before death, 14,15,21,25 whereas only a minority of Ontario residents are followed by palliative care clinicians before they die. 26 This may allay fears that people are turning to MAiD because they cannot access palliative care. It may also suggest that people may be seeking MAiD to alleviate a type of suffering (e.g., existential distress 27 ) that may not be effectively treated by palliative care clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…General PC concerns all patients who have a life-threatening disease or who are at the end of life without complex bio-psycho-socio-spiritual issues. These patients may be cared for by healthcare professionals with basic knowledge of PC (55,56). General PC includes breaking bad news, relief of pain and other symptoms, establishing goals of care, and supporting patients and relatives throughout the continuum of care (6,47,57).…”
Section: Resultsmentioning
confidence: 99%
“…General PC may concern up to 80% of the proportion of patients requiring PC (2). Specialised PC is for patients whose clinical situations are complex and/or unstable, and associated with high level of suffering of the patients and/or their relatives (55,56,58). Specialised PC and treatments should be provided by an interprofessional team, including physicians, nurses, psychologists, social workers, and spiritual assistants, who are specifically trained in PC (47, 57).…”
Section: Resultsmentioning
confidence: 99%